Reezee: Biofrangrance of paddy straw - Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr.; Noor Hasyierah, Mohd Salleh; Mohd Qalani, Che Kasim; Mohd Fahmi, Ramli; Mohd Hafizal, Fazil (Korea Invention News, 2013)
Cyber International Genius Inventor Fair (CIGIF) 2012, 3rd - 9th November 2012 was held at ChungMu Art Hall Convention Centre, Seoul, Korea.